2014
DOI: 10.1242/bio.20148334
|View full text |Cite
|
Sign up to set email alerts
|

Orthosiphon stamineus protects Caenorhabditis elegans against Staphylococcus aureus infection through immunomodulation

Abstract: Amidst growing concerns over the spread of antibiotic-resistant Staphylococcus aureus strains, the identification of alternative therapeutic molecules has become paramount. Previously, we utilized a Caenorhabditis elegans–S. aureus screening platform to identify potential anti-infective agents from a collection of natural extracts and synthetic compounds. One of the hits obtained from the screen was the aqueous extract of Orthosiphon stamineus leaves (UE-12) that enhanced the survival of infected nematodes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 63 publications
2
19
0
Order By: Relevance
“…Therefore, C. elegans is useful as an alternative host to study innate immunity and to screen for pathogenic factors [36]. Our lab, in collaboration with others, successfully used this nematode in the C. elegans infection model to screen and identify new antimicrobial agents and compounds that affect pathogen virulence or modulate the innate immune response of nematodes during pathogen infection [17,[37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, C. elegans is useful as an alternative host to study innate immunity and to screen for pathogenic factors [36]. Our lab, in collaboration with others, successfully used this nematode in the C. elegans infection model to screen and identify new antimicrobial agents and compounds that affect pathogen virulence or modulate the innate immune response of nematodes during pathogen infection [17,[37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCR analysis of the host PMK-1 and DAF-16-regulated antimicrobial genes confirmed a significant positive modulation of these genes in S. aureus -infected worms exposed to O. stamineus extract. Further studies also revealed eupatorin as the major bioactive ingredient that contributed to the immunomodulation effect of O. stamineus (Kong et al, 2014a). In a separate study, O. stamineus extract also modulated the cellular immune response in vitro (Alshawsh et al, 2012).…”
Section: Identification Of Novel Anti-infectivesmentioning
confidence: 97%
“…The authors showed that the protection provided by colistin is dependent on the p38 MAP kinase innate immune pathway, as well as the stress-response mediators, DAF-16/FOXO and SKN-1/Nrf [36]. Another study found that a natural product extract has immunostimulatory activity in C. elegans and protects nematodes from S. aureus infection [37]. …”
Section: Immunostimulatory Compoundsmentioning
confidence: 99%